Wave separation analysis-derived indexes obtained from radial and carotid tonometry in healthy pregnancy and pregnancy-associated hypertension: Comparison with pulse wave analysis-derived indexes - Pereira, María M.; Torrado, Juan; Bock, Joshua; Sosa, Claudio; Diaz, Alejandro; Bia, Daniel; Zócalo, Yanina (Frontiers in Cardiovascular Medicine, 2022)
Background Increased wave reflections assessed by pulse wave analysis (PWA) was proposed as one of the potential culprits of hypertension seen in women with pregnancy-associated hypertension (PAH). However, this statement has never been confirmed with “Wave Separation Analysis” (WSA), a more sophisticated mathematical approach that analyzes the amplitude and interaction between forward and backward aortic pressure waveform components. Objective To characterize potential changes in pressure wave components of PAH compared to healthy non-pregnant (NP) women and women with normal pregnancies (HP) by using WSA and compared these findings with PWA-derived indexes; secondarily, to evaluate differences in WSA-derived indexes between subgroups of PAH (i.e., preeclampsia [PE] and gestational hypertension [GH]). Methods Using radial and carotid applanation tonometry, we quantified in HP (n = 10), PAH (n = 16), and NP (n = 401): (i) PWA-derived indexes; (ii) WSA-derived indexes: forward (Pf) and backward (Pb) waveform components, backward component arrival time (PbAT), reflection magnitude (RM = Pb/Pf) and index [RIx = Pb/(Pf + Pb)]. Results While PAH was associated with a higher Pf compared to HP and NP, Pb and PbAT were similar between the groups. Both GH and PE showed a higher Pf compared to HP, but only PE had a trend of presenting with higher Pb and lower PbAT compared to the other groups. Finally, PAH showed a trend of having lower RM and RIx compared to NP and HP, with no differences between GH and PE. Conclusion PAH was associated with higher Pf, but not higher Pb, compared to NP and HP, although PE also demonstrated a trend of higher Pb.